2016
DOI: 10.1093/ehjci/jew150
|View full text |Cite
|
Sign up to set email alerts
|

Regular endurance training in adolescents impacts atrial and ventricular size and function

Abstract: Cardiac remodelling to long-term endurance exercise in adolescents is manifested by an increase in atrial as well as ventricular dimensions. The physically active group also demonstrated functional remodelling with an increase in TAPSE and systolic RV wall velocity. These findings have practical implications when assessing cardiac enlargement and function in physically active youngsters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
74
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(84 citation statements)
references
References 33 publications
9
74
1
Order By: Relevance
“…In our earlier study, we found a strong correlation between VO 2max and resting cardiac dimensions, and an additionally but weaker correlation to resting RV function (Rundqvist et al, 2016). In our present study, where we assessed the correlation of VO 2max and cardiac parameters immediately after a short maximal exercise test, we demonstrate that LA volume and systolic function such as LVEF were positively correlated to VO 2max , but the strongest correlation to VO 2max was found in LV volume and E/e 0 .…”
Section: Linear Regressionmentioning
confidence: 62%
See 2 more Smart Citations
“…In our earlier study, we found a strong correlation between VO 2max and resting cardiac dimensions, and an additionally but weaker correlation to resting RV function (Rundqvist et al, 2016). In our present study, where we assessed the correlation of VO 2max and cardiac parameters immediately after a short maximal exercise test, we demonstrate that LA volume and systolic function such as LVEF were positively correlated to VO 2max , but the strongest correlation to VO 2max was found in LV volume and E/e 0 .…”
Section: Linear Regressionmentioning
confidence: 62%
“…Recently, we demonstrated considerable cardiac structural remodelling at rest in endurance trained adolescents compared to controls (Rundqvist et al, 2016), suggesting that long-term effects of regular exercise obviously affect cardiac morphology to a higher extent than cardiac function. We found similar responses to exercise in systolic and diastolic parameters in general for both the active and the control groups.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…5,38 In parallel with our results, more pronounced LV and LA morphologic remodeling was found to be associated with better exercise capacity in echocardiographic studies as well. 5,39 Interestingly, fewer data are available about the relationship between cardiac function and exercise capacity. La Gerche et al 5 demonstrated an inverse correlation between LVEF and VO 2 /kg, but they did not find a relationship between LV deformation parameters and exercise performance.…”
Section: Discussionmentioning
confidence: 99%
“…This is contradictory to what has been seen in young healthy individuals and also in an animal model of chronic obstructive pulmonary disease-induced PH. 38 , 39 However, the effects of exercise training on TAPSE in PH are yet to be explored.…”
Section: Discussionmentioning
confidence: 99%